Surfactant-Induced Wettability Alteration - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2009)
Contact of surfactant solution onto rock surface has an important impact on the wettability alteration of the rock. This phenomenon has widely received attention of researchers on the field of EOR (enhanced oil recovery), at which surfactant solution basically has been used as the main injection fluid. However, there has not yet come up with conclusive findings, which is due to the unique characteristics of surfactant used at the oil fields. Therefore, every surfactant needs a particular laboratory evaluation before injected into a reservoir. We have evaluated surfactant-induced wettability alteration by means of contact angle measurement. Three kinds of surfactant have been used in this experiment, namely: TFSA (thin film spreading agent), IFT-R (interfacial tension reduction), and Well Stimulator type of surfactants. Two kinds of rocks namely LS (limestone) and SL (sandy limestone) have also been prepared. Both rocks are originally oil wet. TFSA-LS interaction tend to decrease the oil preferences with time, the contact angle increased 30 degrees after 8 weeks. Whereas TFSA-SL experienced only a little change of contact angle. Contact IFT-R and LS has changed significantly the contact angle to around 51degrees indicating less oil preference. Whereas, IFT-R and SL only changed a bit to less oil wet. The stimulator type of surfactant obviously lessen the oil wet tendency for the both rocks, the contact angles increase from initially around 15 to 35 degrees. In this experiment we found out that all the three surfactants generally tend to change the wettabillity to less oil wet.